An Island in Greece : On the Shores of Skopelos. - Carroll, Michael, 1935- (I.B. Tauris & Co., 2010)
Scattered in a crescent in the sparkling waters of the Aegean, the islands of the Sporades are known to Greek fishermen as 'the gates of the wind'. It was to this unspoilt archipelago that Michael Carroll sailed Astarte, a boat of sleek mahogany with wine-red sails, named after the Phoenician goddess of the moon and the sea. But his dream of travelling where the wind took him, rootless and free, changed when he landed on Skopelos. There, a chance meeting with the charismatic Vangeli led to him buying a piece of land on a remote cove, once the site of an ancient city and the perfect harbour for.